Presentation and outcome of tuberculous meningitis in a high HIV prevalence setting. - Suzaan Marais; Dominique J Pepper; Charlotte Schutz; Robert J Wilkinson; Graeme Meintjes (PLoS ONE)
Background Mycobacterium tuberculosis is a common, devastating cause of meningitis in HIV-infected persons. Due to international rollout programs, access to antiretroviral therapy (ART) is increasing globally. Starting patients with HIV-associated tuberculous meningitis (TBM) on ART during tuberculosis (TB) treatment may increase survival in these patients. We undertook this study to describe causes of meningitis at a secondary-level hospital in a high HIV/TB co-infection setting and to determine predictors of mortality in patients with TBM. Methods A retrospective review of cerebrospinal fluid findings and clinical records over a six-month period (March 2009-August 2009). Definite, probable and possible TBM were diagnosed according to published case definitions. Results TBM was diagnosed in 120/211 patients (57%) with meningitis. In 106 HIV-infected patients with TBM, six-month all-cause mortality was lower in those who received antiretroviral therapy (ART) during TB treatment; hazard ratio = 0.30 (95% CI = 0.08-0.82). Factors associated with inpatient mortality in HIV-infected patients were 1) low CD4(+) count at presentation; adjusted odds ratio (AOR) = 1.4 (95% confidence interval [CI] = 1.03-1.96) per 50 cells/µL drop in CD4(+) count and, 2) higher British Medical Research Council TBM disease grade (2 or 3 versus 1); AOR = 4.8 (95% CI = 1.45-15.87). Interpretation Starting ART prior to or during TB treatment may be associated with lower mortality in patients with HIV-associated TBM. Advanced HIV and worse stage of TBM disease predict in-hospital mortality in patients presenting with TBM.